Association between HLA-A gene polymorphism and early-onset preeclampsia in Chinese pregnant women early-onset - Yuanyuan Zheng; Cui Ma; Xiaowei Liu; Shaowen Wu; Weiyuan Zhang; Shenglong Zhao (BMC Pregnancy and Childbirth, 2020)
Abstract Background Preeclampsia is an idiopathic disease during pregnancy. This study explores the correlation between HLA-A polymorphism and the onset of preeclampsia. Methods The Illumina HiSeq2500 sequencing platform was used to genotyping HLA-A allele in venous blood DNA of 50 preeclampsia pregnant women and 48 normal pregnant women and umbilical cord blood DNA of their children of Han nationality in China. The frequencies and distributions of alleles and genotypes among the mothers and their children were compared between the two groups. The differences of frequencies and distributions of genotypes were compared between the two groups according to the mothers’ genotype compatibility. Results Twenty HLA-A alleles were detected in preeclampsia pregnant women and normal pregnant women; 21 HLA-A alleles were found in preeclampsia group fetuses and 22 HLA-A alleles in control group fetuses. There was no statistical difference in the HLA-A genes’ frequency between the two groups of pregnant women and their fetuses. When the sharing antigen was 1, the number of maternal-fetal pairs in the preeclampsia group was more than that in the control group; the difference was statistically significant (P < 0.05). The frequency of neither mother nor fetus carrying the HLA-A * 24: 02 gene in the preeclampsia group was significantly lower than that in the control group (P < 0.05). HLA-A gene homozygosity in fetuses of early-onset preeclampsia group was substantially higher than that of the control group (P = 0.0148); there is no significant difference in pregnant women’s genes homozygosity between early-onset preeclampsia group and the control group. Conclusions HLA-A * 24: 02 may be a susceptibility gene for early preeclampsia.